Effect of zinc fertilization on growth, yield attributes and yield of wheat (Triticum aestivum) crop under irrigated mollisol - PRAHARAJ, SUBHASHISA; SINGH, ROHITASHAV; SINGH, V K; GOUDA, HIMANSU SEKHAR; SINGH, R K (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted during rabi 2017-18 and 2018-19 to investigate the effects of different methods of zinc fertilization on growth parameters, yield attributes and yield of wheat (Triticum aestivum L.). The experiment was laid-out in a randomized complete block design with 12 treatments and 3 replications. Seed priming as well as soil application was effective in improving emergence count of wheat over control. Soil application of zinc sulphate heptahydrate @ 25 kg/ha could improve growth parameters, yield attributes and yield of wheat while nutripriming and foliar application failed to do so. The study suggested that soil application method alone or in combination with other application methods like nutripriming or foliar application can provide yield advantage of 10-15% over no zinc application. Considering the fact that combination of other application methods with soil application could not improve yield over soil application alone significantly, hence; soil application of 25 kg ZnSO4.7H2O alone can be recommended for achieving higher grain yield under irrigated mollisol.